Answer:
- 3x² + 5x + 1 = 0 simplified
- x = (-5 ±
)/6 roots
Step-by-step explanation:
<u>Given quadratic formula</u>
<u>Standard form</u>
<u>Simplifying</u>
- 3x² + 5x - 5 + 6 = 0
- 3x² + 5x + 1 = 0
<u>Solving</u>
- x = (-5 ±
)/(2*3) - x = (-5 ±
)/6
Answer:
a2
Step-by-step explanation:
you're using the pythagorean theorem
Answer:
Plumber: 13 hours
Plumbing service: 10
Step-by-step explanation:
What you have to find is LCM(least common multiple in order to find the lcm all you have to do is list all the multiples and find their common multiple.
Answer:
multiply each term in the bracket by the expression outside the bracket
:)
Step-by-step explanation: